THE ROLE OF REFLEXIVE MECHANISMS IN THE DECISION-MAKING PROCESS - Maksymchuk, Nadiia (SWorld-Ger Conference proceedings, 2024)
The paper deals with the problems of forming managers' skills in the formation, setting and dynamics of goals, diagnostics and correction of goal formation when choosing means and methods of influence on the individual. Approaches to the study of reflexiv